ANALYSIS OF GAFUR GHULAM'S POETRY - Bakhriddinov Sardor Khamzayevich (Scholar Express Journal, 2024)
This article contains analyzes of the creative poet and writer of the Uzbek people, Gafur Ghulam, from his childhood, adolescence, and his entry into literature, his work, and his work. In the article, you can see the analysis of poetry, i.e. verse
Keywords: poem; Sog'inish; Vaqt